If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xyz = x * 2z Reorder the terms for easier multiplication: 3xyz = 2x * z Multiply x * z 3xyz = 2xz Solving 3xyz = 2xz Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2xz' to each side of the equation. 3xyz + -2xz = 2xz + -2xz Combine like terms: 2xz + -2xz = 0 3xyz + -2xz = 0 Factor out the Greatest Common Factor (GCF), 'xz'. xz(3y + -2) = 0Subproblem 1
Set the factor 'xz' equal to zero and attempt to solve: Simplifying xz = 0 Solving xz = 0 Move all terms containing x to the left, all other terms to the right. Simplifying xz = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(3y + -2)' equal to zero and attempt to solve: Simplifying 3y + -2 = 0 Reorder the terms: -2 + 3y = 0 Solving -2 + 3y = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3y = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 3y = 0 + 2 3y = 0 + 2 Combine like terms: 0 + 2 = 2 3y = 2 Add '-3y' to each side of the equation. 3y + -3y = 2 + -3y Combine like terms: 3y + -3y = 0 0 = 2 + -3y Simplifying 0 = 2 + -3y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| m/-2-3=1 | | y+q+r=p | | 4x-1/1=8 | | x^3-9x=3 | | 2a^2-11a-21=0 | | 5(p+3)+9= | | y=p+q+r | | -1=2(2-x)-3 | | 7(x+1)-3a=5+4(2x-1) | | 58=2(n-3)+5(5n+2) | | 4t+9=8t-15 | | S=2*pi*R*H | | -5+7=11t-25 | | (9x+5)+(7x+10)+(6x+11)=180 | | 100v^2+120v+36=0 | | .7+y=3.14 | | 3m-n=2m+nform | | 2*p-q-2*r=-1 | | 16x+40(x-1)=1(4x-4) | | 11=k-(-16) | | q-13=7=2/3 | | 6x-4x=-6 | | 6/8-4/8x=5/8 | | 2x+36=37 | | X^6/x^4 | | 9p+5.8=8 | | -4(4+n)+2=-2-6n | | 167=6+14-49r | | -2(9m-4)-1=27+10m | | 40p^2+68p+24=0 | | p-2q-r= | | -4v+6v=-6 |